Pertumbuhan Pariwisata Global: Tantangan Untuk Pemasaran Daerah Tujuan Wisata (DTW) - Martaleni Martaleni (Universitas Airlangga, 2011)
The growth of global tourism is an opportunity and a challenge for all parties including the manager of a tourist destination. Designing marketing strategy appropriate destinations will be able to seize opportunities and challenges. This paper studied the situation on the tourist destination (DTW) Malang Raya and aims to provide some marketing strategies that are important in the growth opportunities of global tourism. Important marketing strategy that must be done in Malang tourist destination that is improving the quality of service through increased range of tourist attractions, good supporting facilities and increasing empathy from workers and local residents. Furthermore Malang tourist destination region has potential as a tourist destination for recreation and nature tourism.